Biopharmaceutical characterization of topical liposome formulations bearing 5-fluorouracil - Marija Glavas-Dodov; Emilija Fredro-Kumbaradzi; Sema Calis; Katerina Goracinova; Kristina Mladenovska; Maja Simonoska; Atila A. Hincal (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2003)
Liposome dispersions and liposome gel formulations for topical administration were evaluated as modified release delivery systems for 5-fluorouracil. Drug substance has been entrapped in the internal aqueous compartment of liposomes during the preparation. The concentration of 5-fluorouracil in the hydration medium was varied and the effect on the liposome characteristics was considered. Liposome gel formulations were prepared by incorporation of liophylized liposomes into a structured vehicle of chitosan. The decrease of the amount of aqueous phase bearing total drug quantity (drug/aqueous phase ratio from 1:100, 1:60, 1:40) led to an increase of the percentage of liposome-entrapped drug, and decreased percentage of drug release, while particle size analysis showed no changes in vesicle size. Liposome gel formulations showed initially a higher drug release rate in comparision with liposome dispersions, which could be related to the release of "free" 5-fluorouracil, leaked from liposomes due to the process of liophylization. This was followed by slower release (after 1.5 hour) as a result of the influence of the viscosity of the gel matrix.